2022
DOI: 10.1002/vetr.1737
|View full text |Cite
|
Sign up to set email alerts
|

‘We're gonna end up scared to do anything’: A qualitative exploration of how client complaints are experienced by UK veterinary practitioners

Abstract: Background: UK veterinary practitioners are reported to be fearful of client complaints, but their experiences have not been formally captured. Understanding how complaints impact veterinary practitioners is key to mitigating detrimental consequences. Methods: A qualitative exploration of how UK veterinary practitioners experience and respond to adverse events was conducted. Data were collected via focus groups and interviews, which were transcribed and simultaneously analysed. Coding and theme development wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…10 Gibson and colleagues also found that the emotional burden of client complaints could be exacerbated by practice-and regulator-level complaint investigation and management processes. 7 In particular, the administrative burden associated with investigations and the perception that staff were 'guilty until proven innocent' were identified as key potentiating factors. Participants also reported that the adverse impacts could be influenced by the level of support provided by colleagues and practice managers.…”
Section: What You Need To Knowmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Gibson and colleagues also found that the emotional burden of client complaints could be exacerbated by practice-and regulator-level complaint investigation and management processes. 7 In particular, the administrative burden associated with investigations and the perception that staff were 'guilty until proven innocent' were identified as key potentiating factors. Participants also reported that the adverse impacts could be influenced by the level of support provided by colleagues and practice managers.…”
Section: What You Need To Knowmentioning
confidence: 99%
“…6 Similarly, in a paper summarised on p 160 of this issue of Vet Record, Gibson and colleagues highlight the utility of client complaints for identifying patient safety issues, particularly those at a system level. 7 However, learning opportunities aside, complaints, particularly those perceived to be malicious, were found to be linked to adverse emotional effects such as anger, fear, frustration and a reduction in clinical confidence. 7 These themes are mirrored within the human healthcare literature, where general practitioners described feelings of intense anger (sometimes directed at the patient) or depression (often linked to concerns about clinical ability) after receiving patient complaints.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The distress that can result from feeling responsible for harm to a patient can be considerable, 1 and reputational damage, or fear of it, can also have a negative effect on veterinary professionals' mental health. 2 In addition, there is also a financial burden on the practice due to costs involved in mitigating or rectifying the harm, lost time in dealing with the incident and damage to the relationship with the client. 3 The aim of patient safety systems is to prevent and reduce risks, errors and harm that occur during healthcare provision.…”
mentioning
confidence: 99%